Pengabdian Masyarakat Internasional: Membangun Koneksi Global, Volunteer Pariwisata, Pendidikan dan Kesehatan Internasional - Btari Mariska Puwaamijaya; Syti Sarah Maesaroh; Adi Prehanto; Muhammad Dzikri Ar Ridlo; Ni Wayan Mega Sari Apri Yani; Ni Made Ayu Natih Widhiarini; I Wayan Putra Aditya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This service aims to advance the achievement of Sustainable Development Goals (SDGs) number 4 (Quality Education) and 10 (Reducing Equality) with a focus on developing the competence of foreign volunteers and improving the management of the Widya Guna Disability Foundation. Collaboration between the UPI Tasikmalaya Digital Business Program, the Bali Institute of Tourism and International Business, and PT Medika Nusantara (Medi-Call) is the main vehicle for this activity. The main theme of the service is